2022
DOI: 10.1146/annurev-genom-111521-102452
|View full text |Cite
|
Sign up to set email alerts
|

Five Priorities of African Genomics Research: The Next Frontier

Abstract: To embrace the prospects of accurately diagnosing thousands of monogenic conditions, predicting disease risks for complex traits or diseases, tailoring treatment to individuals’ pharmacogenetic profiles, and potentially curing some diseases, research into African genomic variation is a scientific imperative. African genomes harbor millions of uncaptured variants accumulated over 300,000 years of modern humans’ evolutionary history, with successive waves of admixture, migration, and natural selection combining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 143 publications
1
10
0
Order By: Relevance
“…The deep evolutionary tree within Africa, with more time for recombination to separate linked alleles, combined with complex patterns of admixture across the continent creates highly heterogeneous haplotypes with limited linkage disequilibrium. 2 As further illustrated by the present paper, on average, a genome of African ancestry carries three to five times more variants than those from other ancestries. 7 In concert, there is a similar imperative to develop faster and better methods of accounting for admixture in the context of natural selection by teasing apart local ancestry, i.e., the likely ancestral parental haplotypes at a locus.…”
Section: Main Textsupporting
confidence: 57%
See 2 more Smart Citations
“…The deep evolutionary tree within Africa, with more time for recombination to separate linked alleles, combined with complex patterns of admixture across the continent creates highly heterogeneous haplotypes with limited linkage disequilibrium. 2 As further illustrated by the present paper, on average, a genome of African ancestry carries three to five times more variants than those from other ancestries. 7 In concert, there is a similar imperative to develop faster and better methods of accounting for admixture in the context of natural selection by teasing apart local ancestry, i.e., the likely ancestral parental haplotypes at a locus.…”
Section: Main Textsupporting
confidence: 57%
“…It is now clear that the detailed study of African genomic variation is a scientific imperative. 2 Therefore, the research reported from Fan et al. adds much needed data to our knowledge of African genomes and the information they contain about humanity’s history within Africa.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic heterogeneity in African ancestry is also caused by fewer genetic population bottlenecks and the fact that human evolution began in Africa. This translated to much lower linkage disequilibrium and heterogenous haplotypes due to less genetic recombination ( 53 ). All these factors need to be considered in multi-ancestry analysis of genetic variations in disease and more so in complex diseases such as asthma which are driven by common variants with small effect sizes.…”
Section: Immunogenetics Of Asthmamentioning
confidence: 99%
“…Such data sharing should go hand in hand with plans to promote benefits to participating communities (Ramsay, 2022). Moreover, commercialization of geneomic research products needs appropriate regulation now more than ever as African genomes are likely to become central to major health-related discoveries (Wonkam et al, 2022). Hastiness to once more exploit this unique resource has contributed to legal challenges for an "African" Genome-Wide Association Studies (GWAS) DNA chip that was developed by a company that lacked sufficient engagement with key stakeholders (Stokstad, 2019).…”
mentioning
confidence: 99%